The Probability of Legislative Shirking: Estimation and Validation - Serguei Kaniovski; David Stadelmann (Center for Research in Economics, Management and the Arts (CREMA), 2015)
We introduce a binomial mixture model for estimating the probability of legislative shirking. The estimated probability strongly correlates with the observed frequency of shirking obtained by matching parliamentary roll-call votes with the will of the median voter revealed in national referenda on identical legislative proposals. Since our estimation method requires the roll-call votes as sole input, it can be used even if the will of the median voter is unknown.
Keywords: C13; D72; 330; binomial mixture model; legislative shirking; referenda